(untitled) (REMUNOM, 2024)
The article analyzes suicide rates in Paraná from 2012 to 2022, highlighting the importance of understanding this multifactorial phenomenon to improve public mental health. It provides data that supports the formulation of mental health policies and suicide prevention strategies, while also contributing to new studies on population well-being. Based on information from the Mortality Information System (SIM) and DATASUS, suicides were analyzed according to sociodemographic variables, such as age, sex, race, and educational level, as well as methods used, categorized under ICD10 (X60-X84). The data reveal that suicide rates in the state increased by 46.43% over the decade, with a predominant victim profile of males, aged 20 to 59 years, of white ethnicity, and with incomplete high school education. The analysis further highlights that the Indigenous population shows the highest proportional suicide rates, especially among young people, emphasizing the impact of sociocultural transformations.